Glucagon therapy in acute pancreatitis. Report of a double-blind trial. Issue 3 (March 1978) - Dürr, H K; Maroske, D; Zelder, O; Bode, J C
Abstract : The results of a double-blind trial of glucagon in 69 patients with acute pancreatitis are reported. In a subgroup of 59 patients statistical analysis showed no significant differences between the glucagon-treated (n = 29; 2 X 5 mg protamine-zinc glucagon intramuscularly per day) and the placebo-treated (n = 30) subjects for the following data: duration of pain left spontaneously and induced by palpation, amounts of analgesics and antispasmodics required by the patients, duration of hospital stay, amylase activities in serum and 24 hour urine collections. Mortality rates did not differ significantly between the glucagon-treated and the placebo-treated subjects in the total group of 69 patients and in the two subgroups of patients who were treated conservatively (n = 59) and those who underwent laparotomy because of severe peritonitis (n = 10). From the results of this study it is concluded that favourable effects of glucagon upon the course of acute pancreatitis--if they do exist--are not significant.